2009
DOI: 10.1144/0016-76492009-006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for 930 Ma metamorphism in the Shetland Islands, Scottish Caledonides: implications for Neoproterozoic tectonics in the Laurentia–Baltica sector of Rodinia

Abstract: Zircon and monazite laser-ablation inductively coupled plasma mass spectrometry U–Pb geochronological data for two metasediment samples from the Westing Group, northern Shetland Islands, Scottish Caledonides yield ages between 938 ± 8 and 925 ± 10 Ma (Tonian) for upper amphibolites-facies metamorphism. Texturally early metamorphism is recorded by a migmatitic garnet + sillimanite + plagioclase + muscovite + biotite assemblage, which formed at c . 650–700 °C and 7 kbar. Subsequent rework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 104 publications
5
36
0
Order By: Relevance
“…Also shown in Figure 8 is an additional data point of previously published conventional P-T data (Cutts et al 2009b). …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Also shown in Figure 8 is an additional data point of previously published conventional P-T data (Cutts et al 2009b). …”
Section: Discussionmentioning
confidence: 89%
“…This minor age difference could be the result of partial resetting of older grains, perhaps sourced from older metamorphism in Shetland (e.g. Cutts et al 2009b) or detrital grains. For sample FRQ-20, the older population (c. 474 Ma) was found in cores of large grains and could plausibly have grown at an early stage of Grampian metamorphism in response to a prograde silicate (garnet-bearing) reaction that produced monazite (Hermann & Rubatto 2003;Spear & Pyle 2010; see also Kelsey et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…2) and in correlative successions along northern Laurentia and possibly extending as far as Siberia (Cawood et al, 2016;Likhanov et al, 2015;Malone et al, 2014 (Cutts et al, 2009;Friend et al, 2003;Kirkland et al, 2006;Kirkland et al, 2007;Kirkland et al, 2008;Watt et al, 2000). The units were Balashov et al (1996) reported U-Pb zircon evaporation ages of 1160 ± 40 Ma for mafic and felsic igneous rocks of the Eimfjellet Group, which separates metasedimentary rocks of the underlying Isbjörnhamma and overlying Deilegga groups.…”
Section: Northeast Laurentia -Valhalla Orogenmentioning
confidence: 99%
“…3) may form part of essentially the same sedimentary package. Both successions record evidence for amphibolite-facies metamorphism at c. 930-920 Ma (Cutts et al 2009(Cutts et al , 2011 and incorporate strips of mafic and felsic orthogneisses that have been interpreted as inliers of the Lewisian Gneiss Complex (Flinn & Roddam 1994;Flinn 2014). The Yell Sound Group and the Westing Group are succeeded eastwards by the c. 14 km thick East Mainland Succession consisting of psammites, pelites and marbles with minor volcanic horizons (Flinn 1967), although the presumed intervening unconformity is obscured by high tectonic strain (Flinn 1988).…”
Section: East Of the Walls Boundary Faultmentioning
confidence: 99%
“…The overall tectonic significance of these orogenic events has been much debated, the most recent syntheses suggesting that they correspond to accretionary events along a proximal active margin of the Rodinia supercontinent (Cawood et al 2010(Cawood et al , 2015Kirkland et al 2011). Although there is evidence of Neoproterozoic metamorphism within the Westing Group in western Unst at c. 930 Ma (Cutts et al 2009), younger Cryogenian Knoydartian orogenesis has hitherto been unreported in Shetland. This is important for regional tectonic models, as Knoydartian events are now shown to extend significantly northwards from northern mainland Scotland to Shetland.…”
Section: Evidence For Knoydartian Deformation and Metamorphism In Normentioning
confidence: 99%